Teaching English Language Courses for Tourism and Hospitality Purposes: A Study of Graduates Workplace Needs - Hussam Ahmad Qaddumi; Khaled Mahmoud Masood; Hassan Ahmad Qaddumi; Samir Mohamad Rammal (Researchparks Publishing, 2022)
When taking into account Palestinian tourism sites, mastering language English for instance is a prerequisite for serving and offering tourism services in tourist places such as Bethlehem, Jerusalem, Jericho and Hebron after graduation. In Palestine, English for Specific Purposes especially in hospitality and tourism purposes has not been given much investigation in research. Globally, English language is used as a medium of communication in contexts such as hospitality, travel, and tourism. This study examined how English language is used to prepare tourism and hospitability learners who anticipate serving in Palestinian tourism sites. The data indicated that the learners’ perceptions of the courses offered in English are not consistent with their aspirations and perceived academic English language needs, and their response to how they perceive the importance of English language needs was moderate. Based on these findings, the study suggests restructuring these courses and reconsidering the adopted teaching methods to help learners receive proper instruction geared towards intended learning outcomes and meets their future workplace needs. For future studies, it is recommended that quantitative and qualitative researches are needed to be carried out to analyze the actual needs of undergraduate students to the English language in programs hotel management and tourism.